La acupuntura táctica: características y estrategias de la arquitectura del paisaje urbano para la intervención urbana en el borde natural. Lago Terreros, Altos de Cazuca-Soacha. (2022)
The landscape architecture system develops the design, rehabilitation and conservation of spaces through environmental configuration, meeting ecological and human needs. However, when studying its characteristics, design in the right conditions generates social inclusion, an appropriate way to contribute to sustainability in places that do not have great development is by rehabilitating them with green techniques that establish a local environmental conservation model. This process allows the landscape to be managed for the benefit of society and the values ​​of the environment, increasing safety figures. However, these principles can be linked in a socially marginalized scenario, a sector victim of forced displacement immigration, affected by self-construction housing. The Soacha sector is made up of 87 non-legalized neighborhoods, located in marginal high-risk areas where the highest rate of urban poverty is evident, landscaping is affected by all the displaced people who self-build illegally, even in environmental protection areas, and this determinant generates a high rate of visual pollution.